Surgical Surprise in a Case of Pure esophageal atresia: How High Can the Lower Pouch Be? - Devendra Kumar Yadav; Kashish Khanna; Vikram Khanna; Deepak Bagga (EL-Med-Pub, 2018)
The gap between the upper and lower pouches in case of pure esophageal atresia (EA) is usually long and requires multistaged repair. However, in rare cases, the gap may be short and can be repaired primarily commonly through thoracotomy approach. We report an unusual case of a 2-day-old baby girl who presented with short gap EA where the lower esophageal pouch was found adjacent to the blind upper pouch in the neck and primary repair could be performed through the cervical route itself.